2020
DOI: 10.13171/mjc10202002111248ittz
|View full text |Cite
|
Sign up to set email alerts
|

Phenolic composition and antioxidant potential of different solvent extracts of the endemic Origanum elongatum (Bonnet) Emberger& Maire

Abstract: Plants of the Lamiaceae family are widely used for medicinal, cosmetic and culinary purposes. Phenolic compounds such as flavonoids and tannins are the main constituents of these plants; they have a proven multidirectional biological activity. Polyphenols have exceptional antioxidant potential, and they can intervene in the prevention of many health disorders. This work aims to study the composition and antioxidant power of phenolic compounds from crude extracts and fractions of Origanum elongatum leav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 34 publications
2
5
1
Order By: Relevance
“…These results are in agreement with those obtained by TLC. From Figure 3, it is seen that the antioxidant activity in the extracts is similar to those observed in vitamin C. In general, results of anti-radical activity using the spectrophotometer were in agreement with the assays of total polyphenols and total flavonoids 28 . In addition, our study revealed the behavior of DPPH on our hydromethanol extracts as a function of time.…”
Section: Secondary Metabolitessupporting
confidence: 77%
See 1 more Smart Citation
“…These results are in agreement with those obtained by TLC. From Figure 3, it is seen that the antioxidant activity in the extracts is similar to those observed in vitamin C. In general, results of anti-radical activity using the spectrophotometer were in agreement with the assays of total polyphenols and total flavonoids 28 . In addition, our study revealed the behavior of DPPH on our hydromethanol extracts as a function of time.…”
Section: Secondary Metabolitessupporting
confidence: 77%
“…These extracts were incubated at 3 minutes interval for 15 minutes. The different methods used are the FRAP method, the ORAC, and the radical DPPH • method 28 . The preference for the radical scavenging DPPH • method in the determination of antioxidant activity in compounds or extracts is due to its simplicity and ease of use, its speed, and the formation of a stable radical 29 .…”
Section: Secondary Metabolitesmentioning
confidence: 99%
“…On the other hand (Ramamurthy et al,; 2018) their results came in accord with result of this study 9 . (Tagnaout et al, 2016). Studied the chemical constituents of Capparis spinosa leaf extracts in different solvents 6 .…”
Section: The Chemical Analysismentioning
confidence: 99%
“…(Tagnaout et al, 2016). Studied the chemical constituents of Capparis spinosa leaf extracts in different solvents 6 . The results obtained by them were considerably different from what we found.…”
Section: The Chemical Analysismentioning
confidence: 99%
See 1 more Smart Citation